2016
DOI: 10.1002/2016jd024837
|View full text |Cite
|
Sign up to set email alerts
|

A framework based on 2‐D Taylor expansion for quantifying the impacts of subpixel reflectance variance and covariance on cloud optical thickness and effective radius retrievals based on the bispectral method

Abstract: The bispectral method retrieves cloud optical thickness (τ) and cloud droplet effective radius (re) simultaneously from a pair of cloud reflectance observations, one in a visible or near‐infrared (VIS/NIR) band and the other in a shortwave infrared (SWIR) band. A cloudy pixel is usually assumed to be horizontally homogeneous in the retrieval. Ignoring subpixel variations of cloud reflectances can lead to a significant bias in the retrieved τ and re. In the literature, the retrievals of τ and re are often assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
100
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(102 citation statements)
references
References 32 publications
2
100
0
Order By: Relevance
“…In contrast, total reflectance uncertainty did produce a slight systematic bias of −2.43 % in the polarimetric τ (pol) retrieval that can be linked to the convexity of the single-band LUT used to perform the retrieval. This sort of bias could perhaps be accounted for by introducing a Taylor expansion correction similar to the one discussed in Zhang et al (2016) in the context of unresolved inhomogeneity. Beyond these systematic biases, we found that the induced uncertainties in the bispectral retrievals were δr e = 5 or δτ = 7 %.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, total reflectance uncertainty did produce a slight systematic bias of −2.43 % in the polarimetric τ (pol) retrieval that can be linked to the convexity of the single-band LUT used to perform the retrieval. This sort of bias could perhaps be accounted for by introducing a Taylor expansion correction similar to the one discussed in Zhang et al (2016) in the context of unresolved inhomogeneity. Beyond these systematic biases, we found that the induced uncertainties in the bispectral retrievals were δr e = 5 or δτ = 7 %.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Recently, great effort has been made to account for the influence of the PPH bias on bispectral MODIS retrievals. The 2-D Taylor expansion technique implemented by Zhang et al (2016) offers the possibility of quantifying (and potentially correcting for) the impact of PPH bias on bispectral retrievals. This approach requires high-spatial-resolution measurements in at least one spectral band to obtain the sub-pixel reflectance variability, which is used to determine corrections for the bias of r e and τ .…”
Section: Summary and Discussionmentioning
confidence: 99%
See 3 more Smart Citations